2008
DOI: 10.1016/j.jcis.2007.09.069
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ligand structure on the stability and oxidation of copper nanoparticles

Abstract: The stability and oxidation of copper nanoparticles stabilized with various ligands have been studied. Lauric acid-capped copper nanoparticles were prepared by a modified Brust-Schiffrin method. Then, ligand exchange with an excess of different capping agents was performed.Oxidation and stability were studied by UV-vis, XRD, and TEM. Alkanethiols and oleic acid were found to improve air stability. The oxidation resistance of thiol-capped copper nanoparticles was found to increase with the chain length of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
182
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 247 publications
(195 citation statements)
references
References 46 publications
(47 reference statements)
12
182
1
Order By: Relevance
“…However, very few studies have been reported about photocatalytic performance of Cu NPs in connection with titania [47][48][49]. The main problem with utilizing Cu NPs as a "plasmonic sensitizer" is the known fact that zero-valent copper is easily oxidized and lose plasmon resonance properties gradually under ambient conditions [54][55][56]. For example, (i) although, titania modification by strong radiolytic reduction of Cu 2+ or photodeposition under anaerobic conditions resulted in formation of zero-valent copper, Cu 0 was subsequently oxidized under ambient conditions forming CuO/TiO 2 and Cu/Cu 2 O/Cu/TiO 2 , respectively [57][58][59] and (ii) even Cu NPs immersed in water were oxidized by dissolved oxygen [60].…”
Section: Metallic Copper-plasmonic Photocatalysismentioning
confidence: 99%
“…However, very few studies have been reported about photocatalytic performance of Cu NPs in connection with titania [47][48][49]. The main problem with utilizing Cu NPs as a "plasmonic sensitizer" is the known fact that zero-valent copper is easily oxidized and lose plasmon resonance properties gradually under ambient conditions [54][55][56]. For example, (i) although, titania modification by strong radiolytic reduction of Cu 2+ or photodeposition under anaerobic conditions resulted in formation of zero-valent copper, Cu 0 was subsequently oxidized under ambient conditions forming CuO/TiO 2 and Cu/Cu 2 O/Cu/TiO 2 , respectively [57][58][59] and (ii) even Cu NPs immersed in water were oxidized by dissolved oxygen [60].…”
Section: Metallic Copper-plasmonic Photocatalysismentioning
confidence: 99%
“…Addition of antioxidants, such as ascorbic acid, was shown to sufficiently retard the rate of Cu NPs oxidation [108]. Alkanethiols and oleic acid were also found to improve stability of Cu NPs in air [124]. Deposition of a graphene layer also enables effective protection of a copper core up to 200 ºC in humid air [125].…”
Section: Stabilization Of Metal Nps Against Oxidationmentioning
confidence: 99%
“…However, copper nanoparticles are easily oxidized in air (Park et al 2007;Kanninen et al 2008), thereby spoiling bonding properties. To solve that problem, our research group previously developed methods for fabricating chemically stable copper metal particles.…”
Section: Introductionmentioning
confidence: 99%